Influence of clay mineralogy on undrained cyclic strength of sand with fines - Irem Bozyigit (Engineering Science and Technology, an International Journal, 2024)
Soils in natural or reclaimed areas frequently contain a mixture of sand, silt, and clay, rather than consisting solely of clean sand. The influence of a small proportion of fine plastic particles within a sandy matrix on liquefaction resistance still remains unclear. For this purpose, the cyclic response of sand with clay is investigated by using two different types of clay (kaolin and montmorillonite) with three different clay content (5, 10, 15%). The influence of clay mineralogy and clay inclusion level on the cyclic behavior of clayey sand is analyzed. The specimens are prepared with 50% relative densities using wet tamping method to ensure homogeneity and consolidated at 100 kPa effective stress. The results show that kaolin and montmorillonite contained sand show contractive response and limited flow type of liquefaction. For kaolin containing sand, specimens containing 5% kaolin showed a increment in resistance while liquefaction resistance decreased on specimens that contained 10% and 15% kaolin. When considering specimens with montmorillonite; in sand with a 5% clay content, a decrease in liquefaction potential was observed, while an increment was obtained in sand containing 10% and 15% clay content. Moreover, between the intergranular void ratio and the liquefaction resistance, a significant relationship is revealed.